2022
DOI: 10.1021/acsami.2c01161
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Hierarchical Bonelike Compartmentalized Microconstructs Using Nanogrooved Microdiscs

Abstract: Fabrication of vascularized large-scale constructs for regenerative medicine remains elusive since most strategies rely solely on cell self-organization or overly control cell positioning, failing to address nutrient diffusion limitations. We propose a modular and hierarchical tissue-engineering strategy to produce bonelike tissues carrying signals to promote prevascularization. In these 3D systems, disc-shaped microcarriers featuring nanogrooved topographical cues guide cell behavior by harnessing mechanotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…51 Furthermore, a study utilized the ridge/grooved pattern topodiscs of 944 ± 49/358 ± 23 nm size with 201 ± 45 nm ridge height to facilitate osteogenic differentiation of cultured adipose-derived stromal cells and endothelial cells via a mechano-transduction effect. 52 In conclusion, nanoridge/grooved surface size and depth have been shown to play a significant role in stem cell therapy. Researchers demonstrated that nanoridge/grooved surfaces of different sizes and depths could enhance specific stem cell differentiation.…”
Section: Nanotopographic Patterns For Stem Cell Therapymentioning
confidence: 94%
See 1 more Smart Citation
“…51 Furthermore, a study utilized the ridge/grooved pattern topodiscs of 944 ± 49/358 ± 23 nm size with 201 ± 45 nm ridge height to facilitate osteogenic differentiation of cultured adipose-derived stromal cells and endothelial cells via a mechano-transduction effect. 52 In conclusion, nanoridge/grooved surface size and depth have been shown to play a significant role in stem cell therapy. Researchers demonstrated that nanoridge/grooved surfaces of different sizes and depths could enhance specific stem cell differentiation.…”
Section: Nanotopographic Patterns For Stem Cell Therapymentioning
confidence: 94%
“…The 200 nm deeply grooved surface with 650 nm peak to peak distance showed cellular migration along the grooved surface, osteogenic and adipogenic differentiation effect under the presence of respective differentiation cellular culture mediums . Furthermore, a study utilized the ridge/grooved pattern topodiscs of 944 ± 49/358 ± 23 nm size with 201 ± 45 nm ridge height to facilitate osteogenic differentiation of cultured adipose-derived stromal cells and endothelial cells via a mechano-transduction effect …”
Section: Engineering Nano-biophysical Interactions For Stem Cell Therapymentioning
confidence: 99%
“…Importantly, these nanogrooves stimulate osteogenesis and mineralization independently while providing an ideal environment for the prevascular-like endothelial organization. 154 It has been demonstrated that including lithographically inspired hydroxyapatite (HA)-incorporated polycaprolactone (PCL) parallel nanogrooves and equine bone powder (EBPs) in dental pulp stem cells (DPSCs) synergistically enhances osteogenesis. Surprisingly, the nanogrooves promoted cell elongation, whereas EBPs controlled cell dispersion and aggregation.…”
Section: Surface Nanotopographymentioning
confidence: 99%
“…Also, standalone superhydrophobic surfaces have afforded the fabrication of core-shell and multicompartmental microgels comprising a photo-crosslinkable CHT outer layer and an ALG core, which could be further liquefied giving rise to a liquid microenvironment that enhanced nutrient up-take and disposal of waste products by encapsulated cells ( Costa and Mano, 2017 ). Non-modified CHT and ALG polysaccharides have also been used as layer-by-layer (LbL) building-blocks in the fabrication of either hollow ( Ribeiro et al, 2018 ) or liquefied multilayered capsules ( Nadine et al, 2019 , 2022 ; Bjørge et al, 2022 ), which could be used for tailoring cellular internalization and bone repair, respectively. Recently, the production of marine polysaccharide-based particulate systems through superhydrophobic surfaces expanded beyond the standard spherical-shaped ones.…”
Section: Biomaterials Processing Routes and Their Biomedical Applicat...mentioning
confidence: 99%